Hypoglycemic and Antihyperglycemic Activities of 80% Methanol Root Extract of Acanthus polystachyus Delile (Acanthaceae) in Type 2 Diabetic Rats - Derebe D; Wubetu M; Alamirew A (Dove Medical Press, 2020)
Dagninet Derebe,1 Muluken Wubetu,2 Amare Alamirew1 1Department of Pharmacy, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 2Department of Pharmacy, College of Health Sciences, Debre Markos University, Debre Markos, EthiopiaCorrespondence: Dagninet Derebe Email dagninet37@yahoo.comBackground: The morbidity and mortality rate from diabetic mellitus are increasing in the world especially in low- and middle-income countries; hence, it is necessary to evaluate the efficacy and safety of medicinal plants to support existing drugs in treating diabetes mellitus. Therefore, the aim of this study was to evaluate the hypoglycemic effect of 80% methanol root extract of Acanthus polystachyus in normoglycemic, hyperglycemic, and streptozotocin–nicotinamide induced diabetic rats.Methods: Male albino Wistar rats were divided into five groups (n=6) in all three models. In all models, group one rats served as a negative control and were received vehicle (10mL/kg distilled water), whereas group two (APRE100), three (APRE200), and four (APRE400) were treated with 100, 200, and 400mg/kg of extract, respectively, and group five were treated with glibenclamide (5mg/kg) and served as a positive control. Blood glucose levels were measured at different time points by taking blood from their tails. Data were analyzed using one-way ANOVA followed by Tukey’s post hoc test to carry out comparisons between and within-group and P < 0.05 was considered as statistically significant.Results: The root of Acanthus polystachyus reduces peak blood sugar levels significantly after the loading of oral glucose at all tested doses. In streptozotocin–nicotinamide-induced type 2 diabetic rats, the daily oral administration of the crude extracts showed a significant reduction of blood glucose level at all tested doses compared to the negative control group. However, the extract did not reduce blood glucose levels in normoglycemic rats at all tested doses compared to both negative and positive control.Conclusion: From this study, it can be concluded that the root extract of Acanthus polystachyus showed an antihyperglycemic effect in hyperglycemic and diabetic rats but lack hypoglycemic effect in normoglycemic rats. Hence, the plant root may be a good candidate for the development of new antidiabetic drugs.Keywords: Acanthus polystachyus, antihyperglycemic, type 2 diabetes, streptozotocin, nicotinamide